Green tea halts progression of cardiac transthyretin amyloidosis: an observational report - Kristen, Arnt; Lehrke, Stephanie; Buß, Sebastian Johannes; Mereles, Derliz; Steen, Henning; Ehlermann, Philipp; Hardt, Stefan; Giannitsis, Evangelos; Haberkorn, Uwe; Schnabel, Philipp Albert; Dengler, Thomas; Katus, Hugo (Clinical research in cardiology, 2012)
Background: Treatment options in patients with amyloidotic transthyretin (ATTR) cardiomyopathy are limited. Epigallocatechin-3-gallate (EGCG), the most abundant catechin in green tea (GT), inhibits fibril formation from several amyloidogenic proteins in vitro. Thus, it might also halt progression of TTR amyloidosis. This is a single-center observational report on the effects of GT consumption in patients with ATTR cardiomopathy. Methods: 19 patients with ATTR cardiomyopathy were evaluated by standard blood tests, echocardiography, and cardiac MRI (n = 9) before and after consumption of GT and/or green tea extracts (GTE) for 12 months. Results: Five patients were not followed up for reasons of death (n = 2), discontinuation of GT/GTE consumption (n = 2), and heart transplantation (n = 1). After 12 months no increase of left ventricular (LV) wall thickness and LV myocardial mass was observed by echocardiography. In the subgroup of patients evaluated by cardiac MRI a mean decrease of LV myocardial mass (−12.5 %) was detected in all patients. This was accompanied by an increase of mean mitral annular systolic velocity of 9 % in all 14 patients. Total cholesterol (191.9 ± 8.9 vs. 172.7 ± 9.4 mg/dL; p < 0.01) and LDL cholesterol (105.8 ± 7.6 vs. 89.5 ± 8.0 mg/dL; p < 0.01) decreased significantly during the observational period. No serious adverse effects were reported by any of the participants. Conclusions: Our observation suggests an inhibitory effect of GT and/or GTE on the progression of cardiac amyloidosis. We propose a randomized placebo-controlled investigation to confirm our observation.
Published online: 15 May 2012
Gesehen am 26.06.2018